THE INFLUENCE OF DISCOUNTS, PRODUCT COMPLETENESS, AND LOCATION AGAINST CONSUMER PURCHASE DECISION (VIA GOOGLE FROM): STUDY AT BOOK SALES CENTER KOMPLEK TAMAN PINTAR YOGYAKARTA - Akbar, Aly (Islamicate Institute, 2017)
This article discusses consumer purchase decisions that can be affected by discounts, product completeness, and location. Respondents in this study as many as 100 people. Data were collected using questionnaires in the form of questionnaires. Data analysis technique used is multiple linear regression analysis. The results of this study indicate that the discount variables (X1), product completeness (X2), and location (X3) have a simultaneous positive influence on consumer purchase decision (Y). Based on the results of the data analysis obtained R square value is 0,544, this means 54.4% consumer purchases affected by discount variables, product completeness, and location magnitude influence